Knowledge and understanding of an HIV/AIDS education workshop in a multinational organisation : an evaluation of the AIDS Champions workshop at Shell Southern Africa - Mulenga, Chao Feramo Nkhungulu (Organisational Psychology, 2015)
Bibliography: leaves 105-111.